2018
DOI: 10.3389/fpsyt.2018.00192
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Leaving Children at Home Alone and Their Mental Health: Results From the A-CHILD Study in Japan

Abstract: Leaving children at home alone is considered a form of “neglect” in most developed countries. In Japan, this practice is not prohibited, probably because this country is considered to have relatively safe communities for children. The impact of leaving children at home alone on their mental health is a controversial issue, and few studies have examined it to date. The aim of this study was to examine the impact of leaving children aged 6 or 7 years at home alone on their mental health, focusing on both the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…A cross‐sectional study was conducted by analysing the pooled data of the Adachi Child Health Impact of Living Difficulty (A‐CHILD) study in 2015 and 2017. Details of the A‐CHILD study can be found elsewhere 25‐29 . In short, questionnaires about parenting behaviours and children's health behaviour were distributed to 10 515 caregivers of first‐grade (ie aged 6‐7 years) children in all 69 public elementary schools in Adachi City, Tokyo (5355 in the 2015 survey and 5160 in the 2017 survey).…”
Section: Methodsmentioning
confidence: 99%
“…A cross‐sectional study was conducted by analysing the pooled data of the Adachi Child Health Impact of Living Difficulty (A‐CHILD) study in 2015 and 2017. Details of the A‐CHILD study can be found elsewhere 25‐29 . In short, questionnaires about parenting behaviours and children's health behaviour were distributed to 10 515 caregivers of first‐grade (ie aged 6‐7 years) children in all 69 public elementary schools in Adachi City, Tokyo (5355 in the 2015 survey and 5160 in the 2017 survey).…”
Section: Methodsmentioning
confidence: 99%
“…The focus of this study is to assess the impact of parental migration on the mental health of left-behind children. Most studies suggest that left-behind children are more likely to have mental health disorders, especially conduct problems such as hyperactivity/inattention, and peer relationship problems [ 7 , 8 , 9 ]. A cross-sectional survey showed that, in China, the depressive symptom score of rural left-behind children was significantly higher (40.4%) than that of the non left-behind group (27.8%), and the prevalence of personality symptoms was significantly higher (64.4% vs. 47.6%) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…While data clearly links lack of supervision with unintentional injury in young children (34), its impact on development in young children has not been well-studied. For school-aged children, being left home alone ≥1 day/week increases conduct problems, hyperactivity and intention symptoms, and peer relationship problems compared to well-supervised peers (35,36). More research is needed to inform policies and interventions to support families in creating safe, nurturing environments for their children (37).…”
Section: Discussionmentioning
confidence: 99%